Investigating the microbial and metalloprotease sequestration properties of superabsorbent wound dressings - Gurdeep Singh; Charlotte Byrne; Helen Thomason; Andrew J. McBain (Scientific Reports, 2022)
Abstract Exudate production is a natural part of the wound healing process, however levels of exudate need to be appropriately managed to maintain a moist wound environment which supports healing. An overly-exuding wound creates an environment favourable to bacterial growth. In recent years, a significant increase in commercially available superabsorbent dressings have become available which claim to absorb and retain excess exudate and its components. However, the effectiveness of these dressings in sequestering and retaining bacteria and host-derived proteins has not been compared. We have therefore investigated several superabsorbent dressings for their ability to absorb and retain bacteria (Staphylococcus aureus and Pseudomonas aeruginosa), their impact on bacterial viability, and their ability to sequester matrix metalloproteinases (MMP)-2 and 9 over 7 days. Whilst all dressings could sequester bacteria, some dressings internalised bacteria more effectively. There was considerable variation in bacterial viability within the dressings’ core, as well as differences in bacterial retention. Some dressings effectively internalised and retained bacteria over time, whereas other dressings retained significantly less. These differences were reflected visually using scanning electron microscopy. Most dressings fully sequestered MMP-2 and 9. These data illustrate differences in the ability of superabsorbent dressings to absorb and retain exudate and its components.